2021
DOI: 10.1108/ijrdm-02-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Can offline–online congruence explain online loyalty in electronic commerce?

Abstract: PurposeOne key issue to be addressed in multichannel retailing strategies has to do with ensuring the consistency of the retailer offerings between the brick-and-mortar and the online stores to offer their customers a seamless experience. This study assesses whether perceived congruence may be relevant to identify segments of heterogeneous based on their online loyalty levels as well as other constructs and variables related to the customer relationship with the retailer for two different product categories.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Omnichannel operations necessitate significant investments in technology, people and logistics (Mishra, 2021) and thus are more feasible amongst the larger BM retailers. An effective multichannel strategy results in higher sales and retailer competitiveness (Ruiz-Molina et al, 2021). In the US, with a recovery in progress, offline store revenues were expected to outgrow those of online stores "on a dollar basis" (Stern, 2021).…”
Section: 22mentioning
confidence: 99%
See 2 more Smart Citations
“…Omnichannel operations necessitate significant investments in technology, people and logistics (Mishra, 2021) and thus are more feasible amongst the larger BM retailers. An effective multichannel strategy results in higher sales and retailer competitiveness (Ruiz-Molina et al, 2021). In the US, with a recovery in progress, offline store revenues were expected to outgrow those of online stores "on a dollar basis" (Stern, 2021).…”
Section: 22mentioning
confidence: 99%
“…A global survey found that whilst in November 2020, only 34% of shoppers confirmed considerable "interactions with physical stores", this figure rose to 67% by November 2021 (Capgemini Research Institute, 2022). Moreover, several BM retailers also added online channels "in competition with pure-play e-tailers" (Ruiz-Molina et al, 2021). During SDCC, apart from increased competition, greater operational difficulties and changes in customer profile and behaviour emerge as factors that demand an increase in offline presence by e-tailers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OOCI has been presented as a key perspective in explaining customer behavior (Ruiz-Molina et al, 2021). In this regard, researchers have mainly investigated the relationship between OOCI and consumer behavior, such as the role of channel integration on customers' omnichannel service usage (Shen et al, 2018), customer engagement (Lee et al, 2019), customer loyalty (Quach et al, 2020) and customer retention (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…OOCI has been presented as a key perspective in explaining customer behavior (Ruiz-Molina et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%